ANYBODY LIVING A PRIVATE LIFE IS A BELIEVER IN MONEY. GERTRUDE STEIN, THE GREAT DEPRESSION, AND THE ABSTRACTION OF MONEY - Daugaard, Solveig (The Nordic Journal of Aesthetics, 2020)
The article considers Gertrude Stein’s reflections about the increasing abstraction of economics in response to the Great Depression and Roosevelt’s New Deal in a number of explicitly political pieces from the mid-1930s, including “A Political Series” (1935), and her five brief newspaper commentaries on “money”: ”Money”, “More About Money”, “Still More About Money”, “All About Money”, and “My Last About Money” (1936). The article then relates them to Walter Benjamin’s and Giorgio Agamben’s ideas about the religious implications of the money system that resonate with Stein’s salute to the “believer in money” as security against contemporary authoritarian tendencies. Stein’s opinion pieces argue against taxation, unionism, and public spending, yet also demonstrate the slippery passage between her explicit conservatism, her economic liberalism and her still present radicalism and critique of patriarchal authority as they recycle crucial elements from contemporaneous works such The Geographical History of America (1935) and Everybody’s Autobiography (1937).